2015
DOI: 10.1111/joor.12355
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ experience of partial tooth loss and expectations to treatment: a qualitative study in Danish and Swedish patients

Abstract: Knowledge of impairments, wishes and expectations is essential to make correct decisions regarding oral rehabilitation. The purpose of this study was to investigate discomforts, wishes and expectations in patients' with partial edentulism before entering oral rehabilitation. In Copenhagen, Denmark, and Malmö, Sweden, respectively, 20 patients with partial edentulism seeking rehabilitation were interviewed in a semistructured qualitative manner. The interviews were transcribed and analysed yielding overall doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 20 publications
4
15
0
4
Order By: Relevance
“…To focus on the topic of interest in our study and limiting the amount of data, we used semi‐structured interviews with focus on tooth loss and treatment hereof. The content in the interview guide was based on a prior study, which led to a theoretical framework with the inclusion of the following topics: Patient's explanation of own tooth loss Coping strategies with impairment due to tooth loss Modifying factors influencing impairment due to tooth loss Expectation of treatment Expectation of longevity/survival of the reconstructions …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To focus on the topic of interest in our study and limiting the amount of data, we used semi‐structured interviews with focus on tooth loss and treatment hereof. The content in the interview guide was based on a prior study, which led to a theoretical framework with the inclusion of the following topics: Patient's explanation of own tooth loss Coping strategies with impairment due to tooth loss Modifying factors influencing impairment due to tooth loss Expectation of treatment Expectation of longevity/survival of the reconstructions …”
Section: Methodsmentioning
confidence: 99%
“…In qualitative studies, tooth loss is often shown to be associated with social stigma . Furthermore, patients are often so dissatisfied with their removable dental prostheses (RDPs) that their acceptance is difficult and becoming “an uncertain person” with low self esteem .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Perder um ou mais dentes muitas vezes leva a um declínio da qualidade de vida, incluindo o comprometimento da função mastigatória e da estética, perda de status social, diminuição da autoestima ao enfrentar e ter que gerenciar a ausência do dente. 3,4 Para muitos pacientes, reabilitação oral significa um retorno a um estilo de vida normal, que melhora consideravelmente a qualidade de vida. 3 Essa é a melhor escolha, não em termos de substituição dos dentes perdidos, mas, num sentido mais amplo, de experimentar a restauração da função oral e tudo o que estiver associada a esta.…”
Section: Introductionunclassified
“…3 Preservar estruturas dentais em pacientes parcialmente endêntulos é de fundamental importância, sejam estas associadas ou não ao tratamento endodôntico. 4 Reabilitar associando com endodontia ou implantodontia tem ficado, muitas vezes, restrito ao debate de porcentagens de sucesso e longevidade, mas apesar de terem características muito diferentes, partilham o objetivo comum de servirem de pilar a uma reabilitação. 5 Nesse sentido, esforços constantes têm sido realizados buscando por melhores estratégias restauradoras, para prolongar a permanência da estrutura dental na cavidade bucal, incluindo técnicas de proteção dentinopulpar, que levam em consideração a preservação da vitalidade pulpar.…”
Section: Introductionunclassified